A novel vasculogenic mimicry-related nomogram predicts prognosis in hepatocellular carcinoma - Zhong, Yun; Ding, Fadian; Zhang, Han; Zhang, Denghan; Zhang, Xiang; Weng, Shangeng (Frontiers in Genetics, 2025)
ObjectiveHepatocellular carcinoma (HCC) is the most common type of liver cancer and has a poor prognosis. Vasculogenic mimicry (VM) is an angiogenic process associated with the growth and spread of malignant tumors. In this study, we aim to create a VM-related, gene-based prediction model to evaluate the prognosis and immune infiltration in HCC patients.Materials and methodsA total of 364 patients from the TCGA database and 242 patients from the GEO database with complete clinical information and transcriptome sequencing data were enrolled in this study. LASSO Cox regression analysis was performed to identify VM-related hub genes. Biological process (BP), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, and gene set enrichment analysis (GSEA) were applied to analyze the biological function of the hub genes. The predictive significance of the related gene signature was confirmed in the GSE14520 cohort. RT-PCR and CD31/E-cadherin immunofluorescence staining were applied to elucidate that the VM score can reflect the degree of vasculogenic mimicry within tumors.ResultsThis study found that VM-related genes were enriched in the proteoglycans in the cancer pathway and the VEGF signaling pathway. A predictive signature based on five genes (MAPK3, MAPK1, VEGFA, NOTCH1, and TGFB1) was identified as an independent risk factor for HCC patient prognosis. GSEA revealed that genes that positively correlated with the signature were enriched in the “NOTCH signaling pathway,” which is activated during angiogenesis. Additionally, CIBERSORTx analysis showed that higher expression of the VM score was associated with immune infiltration of naïve CD4+ T cells in HCC. Pearson correlation analysis revealed a positive link between an increased VM score and inhibitory immunological checkpoints (HVEM and PD-1). Furthermore, in vivo experiments have confirmed that the VM score can effectively reflect the degree of vasculogenic mimicry in hepatocellular carcinoma tissue. The nomogram that utilized the VM score and TNM stage to predict the survival probability of individual HCC patients was satisfactory.ConclusionThe VM score and nomogram constructed to predict the survival probability of HCC patients achieved satisfactory outcomes in this study. The relationship between the biological function of the VM score and immune infiltration could potentially serve as a target for tumor therapy in liver cancer.